Mortality due to cervical cancer in a capital of the brazilian Amazon - Silva, Raquel Gomes da; Nogueira, Laura Maria Vidal; Gatinho, Fernanda Gomes; Silva, Kalene Ramos; Santos, Marllon Rodrigo Sousa; Trindade, Lidiane de Nazaré Mota (Revista de Enfermagem da UFPI, 2024)
Objective: To analyze mortality from cervical cancer in the city of Belém-Pará-Brazil. Methods: Epidemiological, cross-sectional, descriptive study with data on mortality from cervical cancer for the period 2013-2020, obtained from the Mortality Information System and made available by the Pará State Department of Public Health. All reported deaths of women living in the municipality of Belém were included. Data were obtained in June 2022. A descriptive analysis of the socio-epidemiological profile was carried out; mortality rates were calculated according to the year of occurrence; and trend analysis was performed using simple linear regression. Results: A total of 695 deaths were analyzed, with the highest proportion identified in women aged between 50 and 69 years old (43%; n=149), housewives (59%; n=410), single women (39.9%; n=277) and low education, proportionally. The rates were high and tended to increase in the series studied. The period 2015-2017 stands out as the most significant indices. Conclusion: The evidence obtained points to a higher proportion of deaths from CC among women with low education, housewives, single women, aged between 50 and 69 years old. The findings suggest improving actions to promote women’s health and prevent cervical cancer, with improvements in screening actions for the disease.